Pengaruh Good Corporate Governance terhadap Financial Distress yang di Kontrol oleh Ukuran Perusahaan pada Perusahaan Industri Sektor Manufaktur di Indonesia - Mohammad Athian Manan; Sri Hasnawati (Penerbit Goodwood, 2022)
Purpose: This research is to confirm the influence of variables good corporate governance on economic issues. This study uses indicators to measure corporate governance variables as follows managerial ownership, institutional ownership, size of the board of commissioners, size of the board of directors, size of the audit committee. Besides that, the financial distress variables are measured using the Springgate method, this study uses firm size as a control variable. Research Methodology: This esearch uses quantitative descriptive and multiple linear regression analyzes and descriptive statistics refined by the SPSS 23. The population of this survey includes 124 manufacturing companies listed on the Indonesian stock exchange between 2016 and 2020. The sample of this study is illustrated by a targeted sample of 42 sample firms. Results :This research has results show that variables related to corporate ownership, managerial ownership, and size of the board of directors have a significant negative impact on financial distress, but that the size of supervisory board, audit committee members and firm size does not affect financial distress. Limitations : The used of the control variable only uses company size, it is hoped that in the next research can add other control variables such as profitability and leverage so that the research results will be diverse and more accurate. Contribution: This research contributes in terms of empirically proving that investors and/or potential investors can use to study the effect of good corporate governance on financial distress which is controlled by firm size.